The Role of Social Workers in Working with Dialysis Patients Who Choose to Live at Risk - Pankhurst, Holly Elaine (Université d'Ottawa | University of Ottawa, 2018)
This study, completed as part of a major research project in the obtainment of a Master of Social Work, examines the role of social workers in working with dialysis patients who choose to live at risk. The objectives of this study were threefold: 1) to explore how social workers perceive and respond to risk within a renal context; 2) to determine what interventions social workers carry out in working with these dialysis patients who choose to live at risk; and 3) to explore the ethical implications of working with these patients. The results indicated that social workers feel their roles are to advocate for dialysis patients who choose to live at risk, collaborate with patients, their families, and the healthcare team, provide information and referrals to patients, and support patients in their decision to live at risk by educating them on the potential consequences. Furthermore, they stated that they support the patient’s families and their healthcare team in helping them understand why the patient may be living at risk and advocate for others to respect the patient’s autonomy. Keyworks: biopower, dialysis, renal disease, risk, social work. Cette étude, complété dans le cadre d’un mémoire pour l’obtention d’une Maîtrise en Travail Social, examine le rôle des travailleurs sociaux en travaillant avec les patients dialysés qui choisissent de vivre à risque. Les objectifs de cette étude étaient triples: 1) explorer comment les travailleurs sociaux perçoivent et réagissent aux risques dans un contexte rénal; 2) déterminer quelles interventions les travailleurs sociaux effectuent en travaillant avec ces patients dialysés qui choisissent de vivre à risque; et 3) explorer les implications éthiques en travaillant avec ces patients. Les résultats indiquent que les travailleurs sociaux estiment que leur rôle est la défense des droits des patients dialysés qui choisissent de vivre à risque, de collaborer avec les patients, leur famille et l'équipe de soins, de fournir des informations et des références au patient et de soutenir le patient dans sa décision de vivre à risque en les éduquant sur les conséquences potentielles. De plus, elles ont indiqué qu'elles soutiennent les familles des patients et leur équipe soignante en les aidant à comprendre pourquoi les patients vivent à risque et en préconisant le respect de l'autonomie du patient. Mots clés: biopouvoir, dialyse, maladie rénale, risque, travail social